Nature's Honey Bee Farm a feasibility study on bee farming - Aspera, Romeo Isaiah (College of Engineering, 2004)
The country is importing on the average of 200-250 tons of honey per year. Local production is only about 50 tons per year. In the Philippines, there are only 328 bee-farms with an estimated total number of colonies amounting to only about 6000. Of the 328 bee-farms, only 10 can be classified as commercial scale producers. Due to the huge gap between supply and demand of bee related products, there is no real competition among bee-farmers. This together with the still huge amount of unsupplied demand offers a good opportunity in setting up large-scale-bee-farm. Expected revenue is expected to be coming from honey (90%), pollen (8%), and beeswax (2%). In the technical study it was found out that the Apis mellifera was the most favorable bee species that can be used in the business. The strategy employed was to limit the number of colonies on the first year, and then go on to full scale production from the second year onwards. The most common bee-hive used in the industry will be used. This is known as the standard Langstroth bee-hive. guidelines for setting-up hives and the overall farm layout was provided. A design of the Facility Layout was also developed. Target production id 36 tons of honey per year which translates to keeping a 1200 colony farm. After all the technical aspects was considered, total investment costs was estimated to be Php10 million for the first year and only Php 6million for the second year. After that, it is expected that the business will generate positive net income, and the company will be self-sustaining. Gross revenue will range from 3.9 million for the first year to 15.9 million for each of the succeeding years. Net income ranges from 0.5 million for the first year and about 9.5 million for each of the succeeding years. After the financial analysis, it was found out that the business is very liquid and stable. Payback period is approximately 2.5 years. Social profitability was also assessed. It was found out that setting-up a bee-farm not only benefits the economy by increasing GDP and employment, but it also profits the environment by promoting biodiversity, and the agriculture by increasing crop yield. In conclusion it can be said that in all aspects setting up a commercial scale bee-farm is feasible.